Impact of Electricity Generation on the Socio-Economic Situation in Uganda - Mwebaza Joel Turiho (Uganda Christian University, 2024)
This research investigates the socioeconomic impact of electricity generation in Uganda, focusing on three critical dimensions: Gross Domestic Product, industry sector performance, and unemployment. Utilizing time series data collected for 15 years (2006 to 2023) from the World Bank and the Uganda Bureau of Statistics. In order to analyze the 15-year timeseries data set, a quantitative research approach was utilized. The study employs econometric analysis among which is regression in order to uncover the relationships between electricity generation and these socioeconomic parameters. The findings of reveal a significant positive correlation between electricity generation and both GDP growth and industrial sector performance, underscoring the essential role of energy infrastructure in fostering economic development and industrial expansion. However, the findings do indicate no statistically significant relationship between electricity generation and unemployment, suggesting that other factors, such as education, economic policies, and labor market conditions, play more pivotal roles in influencing employment levels. Based on these results, the study concludes with policy recommendations emphasizing the need for sustained investment in energy infrastructure, promotion of renewable energy sources, and comprehensive strategies that link energy policies with broader socioeconomic objectives to achieve sustainable economic development.